Evaluation of a Frozen Micro-Agar Plates of MAPt Antibiotic Susceptibility Test for Enhanced Bioterror Preparedness - Shahar Rotem; Ohad Shifman; Ronit Aloni-Grinstein (Antibiotics, 2022)
There is an urgent need for rapid antibiotic susceptibility tests to improve clinical treatment and to support antibiotic stewardship, especially concerning the emergence of multi-drug-resistant bacteria. Nowadays this need is even more profound due to progress in synthetic biology procedures that may facilitate the malicious preparation of engineered antibiotic-resistant pathogens. We recently described a novel, rapid, simple, specific, and sensitive method named a Micro-Agar-PCR-test (MAPt) and showed its performance on clinical as well as environmental samples. The method does not require any isolation or purification steps and is applicable to a wide range of bacterial concentrations, thus allowing a short time to respond within a bioterror event (5–7 h for B. anthracis, 10–12 h for Y. pestis, and 16 h for F. tularensis). Ready-to-use reagents for this assay may add a level of preparedness. We examined the option of freezing pre-prepared MAPt agar plates and thawing them upon need. Our results show that adequate minimal inhibitory concentration (MIC) values are obtained with the use of thawed 6- and 12-month frozen agar plates. The ability to store MAPt micro-agar plates at −70 °C for a year, together with all other reagents required for MAPt, holds a great advantage for bioterror preparedness.